Polish Agriculture on the Road to Sustainable Agriculture - Radlińska, Kamila (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
European Union (EU) agriculture produces food in sufficient quantity and quality, ensuring food security for EU citizens. Financial support mechanisms under the Common Agricultural Policy (CAP) guarantee affordability for consumers and decent incomes for farmers. In 2019. The European Green Deal (EGD) emphasized the importance of agriculture in climate protection. It set a new direction for change, putting EU farms at the center of sustainable food production. All this meant that existing agricultural practices in the EU allowed for high productivity, but also gave space for sustainable practices. The new financial support mechanisms under the CAP for 2023-2027 have focused on financing agricultural practices that protect the environment. The main purpose of the article is to discuss the future directions of agriculture in EU countries. Based on data on the agricultural sector in Poland, it is shown that an important direction of agricultural development is the digitization of farms and villages, which is a prerequisite for the introduction of precision farming practices. On the one hand, this allows to increase yields and reduce the consumption of natural resources, and in the long run increases productivity in agriculture. On the other hand, it facilitates the implementation of ESG reporting.